Asymmetries and economic interaction between Israel and Palestine - Gianni Vaggi; Sara Baroud (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2005)
The long-lasting nature of the Palestinian-Israeli conflict has caused a severe slowdown of economic activity within and between the two economies involved. Palestine is currently afflicted with economic stagnation and structural bottlenecks - namely sharp income reductions, low investors' confidence, and labour market segmentation. Israel must correct a large budget deficit due to a secularly high expenditure on military defence. The former has all the characteristics proper to a Southern low-income economy; while the latter is the most advanced economy of the region, with a well diversified export base and high-tech capacity. Convergence between the two economies seems constrained by exogenous factors and structural impediments. For this reason, we believe that only an immediate effort to help the Palestinian economy recover and an inner industrial boost can restore normal economic activity and allow benefiting from the dynamic gains arising out of North-South interactions. This paper highlights two main points: first, the present arrangements concerning the labour market prevent full use of the Palestinian potential productive capacity and are a hindrance to its short-term recovery. Second, the trade regime between Israel and a future Palestinian State should resemble a Free Trade Area that explicitly takes into account the deep asymmetries dividing the Palestinian and Israeli economies.
Keywords: F15; J41; O24; O5; 330; Israel; Palestine; Middle East; North-South linkages; labour market; EU-MENA Partnership; trade regimes; Internationale Wirtschaftsbeziehungen; Entwicklung; Freihandelszone; Israel; Palästina